Karakteristik Batu Gunung Posi’padang Balla Kabupaten Mamasa Yang Menggunakan Campuran Laston AC-WC - Marten Pampanglangi; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This study aims to utilize the Posi'padang Balla rock in Mamasa Regency and determine the characteristics of the aggregate by using a mixture of Laston AC-WC. The research method used is an experimental method carried out in the laboratory by examining aggregate characteristics, examining asphalt characteristics, filler characteristics, AC-WC mixture composition, making test objects, testing conventional marshall ACWC mixtures, determining optimum asphalt content, and marshall immersion tests for AC mixtures. –WC. The results of the examination carried out in the Road and Asphalt Laboratory, Faculty of Engineering, Department of Civil, Indonesian Christian University Paulus Makassar, through the Marshall Conventional and Marshall Immersion test obtained the composition of the Laston AC-WC mixture, namely the optimum asphalt content of 5.50%, the coarse aggregate fraction 37.2%, the fraction fine aggregate 51.4%, and cement filler fraction 5.4% with values (stability, flow, VIM, VMA, VFB, MQ, IKS) met the 2018 Bina Marga specifications.